2019
DOI: 10.1016/j.tet.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of lindenatriene, a building block for the synthesis of lindenane oligomers

Abstract: Lindenane oligomers isolated from Chloranthus pose significant challenges for chemical synthesis. The structure of a proposed biosynthetic monomer, lindenatriene, was recently called into question. Its attempted synthesis produced a compound whose 1 H NMR spectrum differed significantly from the spectrum of a monomer produced by oligomer pyrolysis. Here we propose that the original structural assignment after pyrolysis was correct and instead the spectra of synthetic materials were misinterpreted. Reanalysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Consequently, the discrepancies between the 1 H NMR chemical shifts reported by Yuan et al and those reported by Kawabata et al raised questions regarding the validity of the proposed biogenetic mechanism. Finally, Martinez et al [ 133 ] re-assessed the literature and NMR data, affirming lindenatriene’s continued relevance as a building block in Kawabata’s original biogenetic hypothesis.
Scheme 2 Proposed tautomerisation of lindenatriene and iso -lindenatriene
…”
Section: Biogenetic Pathways Of Oligomeric Sesquiterpenoids and Merot...mentioning
confidence: 99%
“…Consequently, the discrepancies between the 1 H NMR chemical shifts reported by Yuan et al and those reported by Kawabata et al raised questions regarding the validity of the proposed biogenetic mechanism. Finally, Martinez et al [ 133 ] re-assessed the literature and NMR data, affirming lindenatriene’s continued relevance as a building block in Kawabata’s original biogenetic hypothesis.
Scheme 2 Proposed tautomerisation of lindenatriene and iso -lindenatriene
…”
Section: Biogenetic Pathways Of Oligomeric Sesquiterpenoids and Merot...mentioning
confidence: 99%